(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research reveals that individuals with cardiovascular disease have severe postprandial hypertriglyceridemia and a notable delay in the clearance of postprandial triglycerides. In this investigation, individuals with cardiovascular disease also exhibited increased values of an estimated variable. Data imply that measures linked to postprandial lipemia should be included in the evaluation and treatment of atherosclerosis, and the current study may lead to more focus on the monitoring and management of dyslipidemia in cardiovascular patients